Seroprevalence of antibodies against Brucella canis in dogs of the Pucusana district, Lima, Peru - Zavala C., Magali (2016)
This study aimed to determine the seroprevalence of antibodies against Brucella canis in dogs of the district of Pucusana, Lima, Peru. Blood samples from 202 dogs older than 6 months of age were collected, regardless of breed, sex or reproductive history. The sera was analysed by the technique of agar gel immunodiffusion (AGID). The results showed 21.3 ± 2.9% (43/202) of dogs seropositive for antibodies against B. canis. The variables sex, breed, occurrence of abortion and street presence were evaluated resulting significant association between seropositivity to B. canis and sex (p<0.05).